Engineering 3D-Printed Advanced Healthcare Materials for Periprosthetic Joint Infections - Iván Yuste; Francis C. Luciano; Brayan J. Anaya; Pablo Sanz-Ruiz; Almudena Ribed-Sánchez; Elena González-Burgos; Dolores R. Serrano (MDPI AG, 2023)
The use of additive manufacturing or 3D printing in biomedicine has experienced fast growth in the last few years, becoming a promising tool in pharmaceutical development and manufacturing, especially in parenteral formulations and implantable drug delivery systems (IDDSs). Periprosthetic joint infections (PJIs) are a common complication in arthroplasties, with a prevalence of over 4%. There is still no treatment that fully covers the need for preventing and treating biofilm formation. However, 3D printing plays a major role in the development of novel therapies for PJIs. This review will provide a deep understanding of the different approaches based on 3D-printing techniques for the current management and prophylaxis of PJIs. The two main strategies are focused on IDDSs that are loaded or coated with antimicrobials, commonly in combination with bone regeneration agents and 3D-printed orthopedic implants with modified surfaces and antimicrobial properties. The wide variety of printing methods and materials have allowed for the manufacture of IDDSs that are perfectly adjusted to patients' physiognomy, with different drug release profiles, geometries, and inner and outer architectures, and are fully individualized, targeting specific pathogens. Although these novel treatments are demonstrating promising results, in vivo studies and clinical trials are required for their translation from the bench to the market.